Полио Плус - движење против хендикеп - Грозданова, Елена; Шаврески, Звонко (Ревија за социјална политика/Journal of Social Policy, 2009)
The Coalition "Macedonia Without Discrimination", composed of several civil society organizations working in the field of protection against discrimination, whose Secretariat is managed by Polio Plus - movement against disability, has devotedly worked on the preparation of the Draft Law on Protection against Discrimination. The working group for the drafting of the draft law by the Ministry of Labor and Social Policy included Mr. Zvonko Savreski from Polio Plus and Ms. Mirjana Najcevska from the Center for Human Rights and Conflict Resolution. They had the opportunity to present the comments and remarks of the civil society organizations.